Falsely elevated troponin: rare occurrence or future problem. Issue 6 (1st January 2016) - Nguyen, James; Thachil, Rosy; Vyas, Neil; Marino, Thomas
Abstract : Introduction: Troponins are known to be released in response to cardiac damage and therefore are the biomarkers of choice for the early diagnosis of acute myocardial infarction (AMI), improving outcome in patients presenting with chest pain. However, false results can occur due to interference from other substances in the blood. Case: A 52-year-old male with a past medical history of alcohol abuse, hypertension, and coronary artery bypass graft at age 34 with normal stress test 2 years before presented to the emergency department (ED) complaining of 1 day of non-exertional chest pain with radiation to the neck and left arm. His troponin was elevated to 5 ng/mL in two samples drawn 12 h apart, with normal CK-MB. Renal function was normal. Electrocardiogram (ECG) showed normal sinus rhythm with no ST elevations or depressions. He underwent cardiac catheterization which showed no obstructive lesions. Five years later, he returned to the ED with abdominal pain and shortness of breath. Troponin was elevated and showed no signs of downtrend on repeat every 6 h. ECG was unchanged from 5 years before. He was discharged with a follow-up cardiac computed tomography (CT). Troponin was measured on the day of his scan and remained elevated; he was asymptomatic. Cardiac CT showed unremarkable coronaries and bypass grafts. Given persistently positive troponin in the setting of minimal to no symptoms, he was thought to have falsely elevated troponins. Centrifugation and 2:1 dilution of the sample resulted in the same general value, respectively. Rheumatoid factor and heterophile antibodies were negative. When his blood sample was sent to a different hospital utilizing a three-site immunoassay method, the value was found zero. Discussion: Cardiac troponins (cTn) are structural proteins unique to the heart, not expressed outside of cardiac tissue and have high sensitivity and specificity for myocardial damage. Therefore, it is the test of choice for the diagnosis of AMI. When an increased troponin value is encountered in the absence of myocardial infarction, other etiologies should be explored, including vasculitis, drug abuse, myocarditis, pulmonary embolism, sepsis, and renal failure. If the clinical picture is not consistent with the elevated lab value, it is necessary to think of other causes, including false-positive results. The prevalence of this type of interference is likely to worsen in the future because of the emergence of immunotherapy in the treatment of a wide range of conditions and the use of radiolabeled antibodies in diagnosis using immunoscintigraphic procedures. Therefore, it is important to consider this as part of the differential.